ALL Repair and Reconstruction: Techniques From the SANTI Study Group - Graeme P. Hopper MD; Thais Dutra Vieira MD; Alessando Carrozzo MD; Edoardo Monaco MD, PhD; Steven Claes MD; Adnan Saithna MD; Camilo P. Helito MD; Etienne Cavaignac MD, PhD; Bertrand Sonnery-Cottet MD, PhD (Video Journal of Sports Medicine, 2023)
Background: Combining an anterior cruciate ligament (ACL) reconstruction with an anterolateral ligament (ALL) reconstruction results in significant advantages including reduced graft rupture rates, a lower risk of reoperation for secondary meniscectomy, improved knee stability, and higher rates of return to preinjury levels of sport. Indications: The previously reported indications for combined ACL and ALL reconstruction are as follows: ACL reconstruction revision; high-grade pivot shift test; long-term ACL rupture; young patients; pivoting activities; concomitant medial meniscus repair, and, specifically, regarding the ALL repair, it must be an acute surgery (within 15 days from injury). Technique Description: Several modern techniques have been described to repair and reconstruct the ALL. This technical note details a number of these techniques performed by the Scientific Anterior Cruciate Ligament Network International (SANTI) Study Group. Results: First, we describe a combined ACL reconstruction and double-bundle ALL reconstruction using hamstring autograft. Secondly, we describe a single-bundle ALL reconstruction using gracilis autograft. Thirdly, we describe an ALL reconstruction technique using a knotless soft anchor, which provides shallow fixation and prevents tunnel convergence. Finally, we describe a technique for ALL repair. Conclusion: Several techniques have been described to repair and reconstruct the ALL, all offering significant advantages over an isolated ACL reconstruction. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.